Determinants of Farmers Preference to Coffee Market Outlet in Jimma Zone: The Case of Coffee Potential Districts (Global Journal of Management and Business Research, 2016)
Abstract not found
Keywords: marketing outlet; cross sectional; multinomial logistic; formal traders; informal buyers; brokers